Verses in Honour of John Sobieski: The Possibilities of Figurative Poetry in the Seventeenth Century - Nedzinskaitė, Živilė (Senoji Lietuvos literatūra, 2015)
John III Sobieski, King of Poland and Grand Duke of Lithuania, was the addressee of probably the largest number of dedications of occasional works in seventeenth-eighteenth-century Lithuania and Poland. Such an outburst was triggered by important victories achieved by this ruler: the Battle of Khotyn in 1673 and especially the victory against the Turks in the Battle of Vienna in 1683. The latter prevented the march of the Turks to Europe and therefore John III Sobieski was called not just a courageous military leader, but also a defender of Christianity and faith. One of the more inventive ways of panegyric writing that demanded special skills and ingenuity of authors was figurative poetry. Born in Antiquity and not forgotten in the Middle Ages, figurative poetry (carmen figuratum) was as though reborn and flourished in the Baroque epoch. Thanks to that the qualities of figurative poetry were discussed and studied in theoretical works of that time. One of the most important among such works was the textbook Poesis artificiosa by the Carmelite monk Paschasius (1637–1692) published in Wȕrzburg in 1668. The paper discusses and analyzes figurative acrostic works dedicated to John Sobieski, which were published not as individual panegyric texts but were integrated into works of diverse nature. The paper focuses on two texts, one in the shape of a sword and one shaped like a flag, by the Piarist monk Ignacy Krzyżkiewicz (1640–1695) published in the textbook of literary theory Attica Musa (Krakow, 1674). They are an excellent reflection of the synthesis of image and word that was so common in the Baroque epoch. Krzyżkiewicz’s text in the shape of a sword is an acrotelestic: the opening and closing letters of its lines form the words ‘Ioannes Sobiescius rex strenuus’ (Jan Sobieski, a courageous ruler). The poem itself is based on a very short story about how the Poles, led by their ruler, defeat the Turks whose fleeing commander is symbolised by the Persian ruler Xerxes. The readers are free to interpret and understand the figurative content of the poem in a personal way. The sword may be seen as a symbol of defence of the homeland, or of an attack on and annihilation of the enemy, or maybe the literary text can serve as the image of the sword of justice and faith in Sobieski’s hand. Finally, the sword is a metaphor of the king himself, of the defender of faith and homeland. In the flag-shaped acrostic the first letters form the words ‘Ioannes Sobiescius, rex Poloniae 3’ (John Sobieski, King of Poland III). It reiterates the idea of the king’s courage on the battlefield. One might assume that the text written in the shape of a flag is the symbol of Sobieski’s victory with which he, like Constantine the Great, not only defeated the enemy of Christianity on the battlefield, but also consolidated the positions of the true faith. As soon as it appeared, Krzyżkiewicz’s work Attica Musa became popular and was read and studied not only by the Piarist monks but also in the schools of other religious orders. In a number of seventeenth-eighteenth-century manuscripts of lectures in rhetoric the examples of Krzyżkiewicz’s figurative poetry were pointed out as models of a certain type of a figurative text and an example to follow. There can be no doubt that this work influenced further development of seventeenth-eighteenth-century artificial poetry